US Land-Grant Universities in India: Assessing the consequences of agricultural partnership, 1952–1972. (March 2017) - Mehta, Simi; Lal, Rattan; Hansen, David
Highlights: India has been an agrarian economy since ancient times and the science and art of agriculture, animal husbandry, soil management and irrigation have richly evolved through the course of its history. The present study illustrates the ways in which these were impacted by the colonization of the country, the subsequent Independence in 1947 amid the complex environment of the Cold War and India's policy of Non-Alignment. Amid a difficult socio-economic situation enraged by the famines and food insecurity in India and the simultaneous Four Point Program of President Harry S. Truman, there emerged a consensus between the two countries to improve the living standards, eliminate hunger, encourage education in food production and food utilization in India with the help of Land-Grant Universities, by creating similar education centers in India. This study of Indo-American partnership in agricultural education, research and extension also incorporates a discussion of the extraordinary role of the Ford and Rockefeller foundations, CIMMYT, IRRI and ICRISAT whose joint efforts with Indian scientists helped build solid foundations for agricultural universities in India, attain self-sufficiency in food grain production and proved to be the harbinger of a new era of Indo-US relations through the Green Revolution. Abstract: India has been an agrarian economy since ancient times and the science and art of agriculture, animal husbandry, soil management and irrigation have richly evolved through the course of its history. The present study illustrates the ways in which these were impacted by the colonization of the country, the subsequent Independence in 1947 amid the complex environment of the Cold War and India's policy of Non-Alignment. Amid a difficult socio-economic situation enraged by the famines and food insecurity in India and the simultaneous Four Point Program of the then President of the United States, Harry S. Truman, there emerged a consensus between the two countries to improve the living standards, eliminate hunger, encourage education in food production, food handling, food utilization and hence development in India with the help of Land-Grant Universities, by creating similar education centers in India. This study of Indo-American partnership in agricultural education, research and extension through the also incorporates a discussion of the extraordinary role of the Ford and Rockefeller foundations as well as that of CIMMYT (International Maize and Wheat Improvement Center), IRRI (International Rice Research Institute) and ICRISAT (International Crops Research Institute for the Semi-Arid Tropics), whose joint efforts with Indian scientists helped build solid foundations for agricultural universities in India, attain self-sufficiency in food grain production and proved to be the harbinger of a new era of Indo-US relations through the Green Revolution.